2012
DOI: 10.1093/carcin/bgs310
|View full text |Cite
|
Sign up to set email alerts
|

GBP-1 acts as a tumor suppressor in colorectal cancer cells

Abstract: The human guanylate-binding protein 1 (GBP-1) is among the proteins the most highly induced by interferon-γ (IFN-γ) in every cell type investigated as yet. In vivo, GBP-1 expression is associated with the presence of inflammation and has been observed in autoimmune diseases, inflammatory bowel diseases (IBD) and cancer. In colorectal carcinoma (CRC), the expression of GBP-1 in the desmoplastic stroma has been previously reported to correlate with the presence of an IFN-γ-dominated T helper type 1 (Th1) micromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 58 publications
4
98
1
Order By: Relevance
“…Similar antipathogen effects have been observed with mouse GBPs (mGBPs), indicating that GBPs exert conserved functions in humans and rodents (9,(31)(32)(33). In addition, GBP-1 is both necessary and sufficient for the inhibitory effects of IFN-␥ on cell proliferation, migration, and invasion, as shown in endothelial cells and epithelial tumor cells (17,19,(34)(35)(36)(37). Of note, the putative murine homologue of human GBP-1, mGBP-2, has also been shown to inhibit cell motility (38).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Similar antipathogen effects have been observed with mouse GBPs (mGBPs), indicating that GBPs exert conserved functions in humans and rodents (9,(31)(32)(33). In addition, GBP-1 is both necessary and sufficient for the inhibitory effects of IFN-␥ on cell proliferation, migration, and invasion, as shown in endothelial cells and epithelial tumor cells (17,19,(34)(35)(36)(37). Of note, the putative murine homologue of human GBP-1, mGBP-2, has also been shown to inhibit cell motility (38).…”
supporting
confidence: 55%
“…Furthermore, an expression vector for the GFP-GBP-1 fusion protein (F-GFP-GBP-1) was generated with the pMCV1.4 construct as previously described (42). Additionally, the sequence of GBP-1 was inserted in frame into the pMCV2.2-Flag vector using the EcoRI restriction site (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that mGBP2 and mGBP5 could promote bacteriolysis by controlling the activation of the inflammasome protein, AIM2, in mouse bone marrow-derived macrophages (36). In human cells, hGBP1 shows one of the highest induction levels in response to IFN-γ stimulation (37), which has been shown to be associated with viral infections, inflammatory bowel diseases, glioblastoma, and cutaneous lupus erythematosus (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…33 In colorectal cancer, GBP1 overexpression in tumor stroma inhibits tumor growth and correlates with improved survival. 34,35 The functions of other GBPs are less clear although animal and in-vitro models suggest a protective role in controlling infection and autoimmunity as GBPs are essential for formation of the inflammasome complex. 36 The inflammasome complex promotes inflammatory cell death through activation of cysteine protease caspase-1 and is purported to have tumor suppressive effects in some studies.…”
Section: Discussionmentioning
confidence: 99%